The Effect Of Financial Performance On Investor Response Before And After Stock Split In Companies Listed On The Indonesian Sharia Stock Index - Achmad Rofi'i; Rahma Yudi Astuti (University of Darussalam Gontor, 2023)
The good or bad financial condition of a company can be seen through the financial performanceof the company. Financial performance can affect the response of investors in investing their funds in thecompany. Against the company. The high investor interest in the company's securities will affect the high shareprice owned by the company so with the high share price, there will also be high risks that investors are concernedabout. Information related to corporate actions is needed by companies to overcome the problems that occur incompanies that affect the optimization of company-owned securities. Stock Split is one of the corporate actionsthat can be implemented by the company to optimize the company's shares. This study aimsto determine theeffect of financial performance as measured by ROA, ROE, and PER on investor response. And whether thereare differences in financial performance and investor response represented by stock returns before and afterdoing a Stock Split. This study uses secondary data, namely the financial statements of companies listed in thesample on the Indonesia Stock Exchange (IDX). This study uses purposive sampling with a total of 28companies. The data analysis method used is multiple linear regression and ANOVA test in SPSS. The resultsof this study indicate that there is no effect of ROA and ROE on investor response as measured by stock returns.However, there is a significant effect of PER on investor response as measured by stock returns. The results ofthe difference test conducted show that there are differences before and after the stock split.